Phytochemical study and antioxidant activity of the heartwoods of Artocarpus Scortechinii King - Wan Norhidayah Wan Seman, 1994- (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Sains (Kimia)) - Universiti Teknologi Malaysia, 2017